Understanding the Impact of Social Capital on Entrepreneurship Performance: The Moderation Effects of Opportunity Recognition and Operational Competency - Xie, Gui-hua; Wang, Lin-ping; Lee, Bey-fen (Frontiers in Psychology, 2021)
Social capital, which is derived from psychological research, has an important value in the construction of network relationships in enterprises. It influences the direction and tendency of network connections in start-up enterprises, and has gradually become an important factor in the study of entrepreneurship by scholars. However, the relationship between this and the effectiveness of innovation is unclear. In this study, social capital is divided into combined social capital and bridging social capital, and specific data of agricultural entrepreneurs are collected through questionnaire surveys. The results show that both combined and bridging social capital have a significant positive effect on agricultural entrepreneurship performance. The entrepreneurial capacity of agricultural entrepreneurs regulates the relationship between social capital and creative performance. In the relationship between integrated social capital and creative performance, operational capacity plays a positive role and opportunity capacity plays a negative role. On the other hand, in the relationship between bridging social capital and creative performance, the opportunity capacity plays a positive role and the operational capacity plays a negative role. Finally, based on the above findings, this study proposes theoretical and practical implications and suggestions for follow-up research.